TORAKOCHIRURGIAManagement of laryngotracheal stenosis - Szyfter, Witold; Wierzbicka, Małgorzata; Popko, Mariola; Pastusiak, Tomasz; Balcerowiak, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduce: Laryngotracheal stenosis (LTS) is a rare condition, but with a still growing number of cases, mostly due to tracheotomy, intubation, irradiation and larynx surgery and iatrogenic sequels. The treatment of LTS is basically surgical with different techniques proposed. Aim: To present and analyze surgical techniques and results of treatment of laryngeal and laryngotracheal stenosis in the Department of Otolaryngology, Poznan University of Medical Science, Poland in a period of ten years. Materials and Methods: The clinical records of 124 patients with LTS (in the period 1999-2008) were reviewed, analyzing retrospectively the following variables: age, gender, localization and grade of stenosis, comorbidities (diabetes, obesity, gastrooesophageal reflux) and outcome of treatment estimated according to medical research council dyspnoea scale. Patients were divided into 4 groups: I – endoscopic management with dilatation (41 patients), II – endoscopic management with laser vapour (30 laser), III – laryngofissure with Montgomery T-tube insertion (35 patients), IV – tracheal resection with termino-terminal anastomosis (5 patients), laryngotracheal resection with cricotracheal or thyrotracheal anastomosis (7 patients). Results: Among 124 patients with LTS, of the medium age of 48 years, 63 were male, 59 female. Localization of the stenosis was as follows: glottic-subglottic in 77, subglottic in 12 and tracheal in 35 patients. The stenoses were assessed as stage I in 5, stage II in 37, stage III in 45 and stage IV in 37 patients according to Cotton grading system. Out of a total of 124 patients 46 had previous tracheotomy, in 11 decannulation eventually failed. In the endoscopic management group 6 patients needed repeated procedures. In the laryngofissure group of 35 patients, 12 had to have tracheotomy maintained. In the group of segmental resection (12 patients) 5 patients had a short segment stenosis, 7 long segment stenosis (more than 4 cm). Patients treated with segmental resections had a favourable outcome, all were decannulated and asymptomatic after a mean follow-up of 12 months. Conclusions: The fundamental treatment of tracheal stenosis is the surgical approach. The endoscopic management (dilatation and laser) need repeated procedures and in some cases tracheotomy had to be maintained. Better recovery, short hospitalization and excellent results were obtained with the cricotracheal segmental resection. Cricotracheal resection is a reliable and versatile technique for the reconstruction of the subglottic airway, almost regardless of the underlying cause. Segmental resection is the treatment of choice in LTS, making the laryngofissure technique obsolete.